Leisure and meaning in life - Iso-Ahola, Seppo E.; Baumeister, Roy F. (Frontiers in Psychology, 2023)
Abstract How people engage in leisure is an important but frequently underappreciated aspect of meaning in life. Leisure activities range from highly engaging and meaningful to subjectively trivial. Leisure itself is largely defined by meaning: The essence of leisure lies less in the specific activity than in the subjective perception of freedom, choice, and intrinsic motivation. People desire their lives to be meaningful, and leisure activities offer varying degrees of satisfying the basic needs for meaning (here covered as purpose, value, efficacy, and self-worth). Leisure activities vary along multiple conceptual dimensions, such as active vs. passive, seeking vs. escaping, solitary vs. interpersonal, and we consider the implications of these for meaningfulness. The most common leisure activity in modern society, watching television, encapsulates some of the paradoxes of leisure and meaningfulness. The study of how leisure enhances meaning in life is rich and ripe for future research.